Impact of AI-powered chatbot choki on Shopee users' continuance intention - Ivana Ester Claudia; Syti Sarah Maesaroh; Muhammad Rizki Nugraha (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
Indonesia’s fast-growing digital economy is driving e-commerce firms to adopt artificial intelligence (AI) to enhance their services. One common tool is the AI-powered chatbot, which helps users quickly and efficiently. Shopee introduced its AI-powered chatbot, Choki, to facilitate seamless, automated customer interactions. This study examines the impact of system quality, information quality, and service quality on user satisfaction and, in turn, on continuance intention. Data were collected from 242 Shopee users in the Jabodetabek region and analyzed using SEM-PLS. The findings reveal that system quality has a significant effect on continuance intention, while information and service quality indirectly affect it through user satisfaction. These results highlight the crucial role of AI-driven system reliability in sustaining users’ long-term engagement with e-commerce platforms. Theoretically, this research strengthens the application of the DeLone and McLean Information Systems Success Model in the e-commerce context, while practically offering practitioners insights to enhance user experience by improving chatbot information accuracy and service responsiveness